(untitled) (Experimental biology, 2022)
Whole-genome sequencing of the SARS-CoV-2 virus during the pandemic has become an essential part of the epidemiological control of the spread of coronavirus infection. This made it possible to get actual data of circulating genetic variants and mutational changes of SARS-CoV-2 during the pandemic. The obtained results provided an opportunity for researchers to collect additional data to evaluate the virulence, infectivity, and the likelihood of evading an immune response when using vaccines and therapeutic monoclonal antibodies. There are different technological approaches for whole-genome sequencing of SARS-CoV-2, but multiplex PCR amplification is used most often due to ease of implementation and cost-effectiveness. When performing research on viral genome sequencing, researchers need to optimize existing sequencing protocols with available reagents or develop new approaches. This study is devoted to the development of a protocol for whole-genome sequencing of the SARS-CoV-2 virus based on the use of RT-PCR amplification using 39 primer pairs in 3 reaction mixtures. The protocol made it possible to obtain 15 complete genome data of the SARS-CoV-2 and can probably be used for large-scale studies on viral genome sequencing.